(3JQcjH GdYjf hYddgG hYdGLgGs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s ((3YHO GdQMef Hf jhfS GdCfUGQi s)
(3ChdgG (B:s
(3Efg jfHZi def GQGO EMcGe eYQaI YdGL Ydd GdYjf Cf jchf HWHjYJgG YGQakG s
(3BNQgG (B:s
(3hef TCf gPG GdTjGa Cf jLdh HjGV BKGQ GdbQhM , agPg GdCOhjI gi GdJi CKHJ PcQgG hCfG CSCdc Gddg Cf jMaXc hjfaYc hCSCdc Cf JLYd ecGaCJi MSf GdOYGA s
(3Vef eLehY , JQJjHgG (B: (3ef U (B310 - (3U(B383s
(3Cdag Ydi QCi CHbQGW hLGdjfhSs
(3hgh YTQ ebGdGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
Keywords: (3GdWHs